Femtosecond infrared spectroscopy of chlorophyll f-containing photosystem I - Zamzam,N; Kaucikas,M; Nurnberg,D; Rutherford,AW; van,Thor J (Physical Chemistry Chemical Physics, 2019)
The recent discovery of extremely red-shifted chlorophyll f pigments in both photosystem I (PSI) and photosystem II has led to the conclusion that chlorophyll f plays a role not only in the energy transfer, but also in the charge separation processes [Nürnberg et al., Science, 2018, 360, 1210–1213]. We have employed ultrafast transient infrared absorption spectroscopy to study the contribution of far-red light absorbing chlorophyll f to energy transfer and charge separation processes in far-red light-grown PSI (FRL-PSI) from the cyanobacterium Chroococcidiopsis thermalis PCC 7203. We compare the kinetics and spectra of FRL-grown PSI excited at 670 nm and 740 nm wavelengths to those of white light-grown PSI (WL-PSI) obtained at 675 nm excitation. We report a fast decay of excited state features of chlorophyll a and complete energy transfer from chlorophyll a to chlorophyll f in FRL-PSI upon 670 nm excitation, as indicated by a frequency shift in a carbonyl absorption band occurring within a 1 ps timescale. While the WL-PSI measurements support the assignment of initial charge separation to A−1+A0− [Di Donato et al., Biochemistry, 2011, 50, 480–490] from the kinetics of a distinct cation feature at 1710 cm−1, in the case of FRL-PSI, small features at 1715 cm−1 from the chlorophyll cation are present from sub-ps delays instead, supporting the replacement of the A−1 pigment with chlorophyll f. Comparisons of nanosecond spectra show that charge separation proceeds with 740 nm excitation, which selectively excites chlorophyll f, and modifications in specific carbonyl absorption bands assigned to P700+ minus P700 and A1− minus A1 indicate dielectric differences of FRL-PSI compared to WL-PSI in one or both of the two electron transfer branches of FRL-PSI.